Diseño de un sistema de control de inventarios para el cormercial Los Nevados ubicado en el cantón Latacunga provincia de Cotopaxi. - Chasiquiza Pullupaxi, Meliza Marilú (2020)
The main objective of this integration project was the design of an inventory control system establishing an ABC classification of the stock in the Commercial "Los Nevados" in Latacunga City, the lack of an inventory control system in hardware stores has caused the deterioration of the articles, the oxidation of several materials, incorrect warehouse registration; which has a negative impact on the administration. Through the scientifictechnical foundation, important concepts concerning inventories and their control were considered. The methodology used had some quantitative and qualitative approaches related to the techniques of collection of information such as the survey, interview and observation; the results obtained through the use of the instruments that are the questionnaire, an open question test and the check list for the physical taking of the inventory, gave as a result relevant information used in the development of the inventory control system classified by families based on their level of commercialization, in a certain period of which it is segmented in three groups A, B, or C as it corresponds, making emphasis in managing the order and classification with the Pareto's diagram (80- 20); which facilitated the administration of the merchandise reducing expenses and losses, avoiding the stagnation of the same one, promoting new strategies and the correct decision making on the permanent control of the entrances and exits of the articles. A manual of functions and procedures was established attributing an adequate management of the inventories that are designed in a flow chart, delimiting the processes that the merchandise must fulfill from the moment that it enters the commercial by the supplier, storage in the different ships and delivery to the client which facilitated and improved the management in the Commercial "Los Nevados".